Analysis of the Effect of Fixed Asset Intensity, Leverage, and Liquidity on Fixed Asset Revaluation in Manufacturing Companies Listed on the Indonesia Stock Exchange - Mustafa Hidayat Nasution; Saparuddin Siregar; Khairina Tambunan (Jurnal Impresi Indonesia, 2024)
Fixed asset revaluation has become an important issue in corporate financial management, especially in the midst of uncertain economic conditions. Manufacturing companies, which are one of the pillars of the Indonesian economy, must be able to manage their fixed assets to improve financial performance and competitiveness. This study aims to determine the effect of fixed asset intensity, leverage, and liquidity on fixed asset revaluation in manufacturing companies listed on the Indonesia Stock Exchange. The research method used is quantitative, with the population and sample in the form of annual reports from 10 manufacturing companies during the 2016-2021 period. Sampling was done by purposive sampling, and data were collected through financial statement documentation. Data analysis was carried out using the linear analysis method using panel data. The results showed that fixed asset intensity has a positive and significant effect on fixed asset revaluation. This is evidenced by the t count value of 3.637 which exceeds the t table 2.003, as well as a probability value of 0.0069 <0.050. Leverage and liquidity also show a positive and significant influence on the revaluation of fixed assets. Simultaneously, the three variables have a significant effect on the revaluation of fixed assets, with a value of F count 4.315 which exceeds F table 2.77 and a probability of 0.000136 < 0.05.